Character Building and Discipline in Adolescents: A Case Study at Bunga Sejati Pencak Silat School, Tantan Village, Muaro Jambi Regency - Bangkit Yudho Prabowo; Dede Dede; Reza Hadinata; Ely Yuliawan (UNIB Press, 2026)
This study aims to describe and analyse the process of character building for discipline among adolescents at the Bunga Sejati Ranting Tantan Pencak Silat Academy, Tantan Village, Muaro Jambi Regency. The study uses a qualitative approach with a case study design to gain an in-depth understanding of the coaching practices that take place in real life at the pencak silat academy. The research participants consisted of six key informants, namely the Village Head, administrators, coaches, community leaders, and two active students. Data were collected through in-depth interviews, participatory observation, and documentation, then analysed using NVivo software through the stages of open coding, axial coding, and thematic analysis. The results of the study identified six main themes in discipline character building, namely Regular Training, Strict Rules, Exemplary Coach, Punctuality, Responsibility, and Respectful Attitude. The findings show that regular training is the foundation for building discipline through consistent habituation, supported by the application of strict rules and the exemplary behaviour of coaches as social models. This process resulted in tangible behaviours such as punctuality, responsibility towards obligations, and a respectful attitude towards coaches and fellow members. Character building at this academy is carried out systematically and holistically by integrating physical, mental, and spiritual aspects. This study provides empirical contributions to the development of character education based on traditional martial arts and serves as a reference for community-based youth development programmes at the local and national levels.